Hydrodynamic Interaction of Three Floating Structures - Abdul Halim, Muhammad Farid; Koto, Jaswar (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
This study will highlight the motion characteristics of single body and multiple bodies of offshore structures due to the effect of hydrodynamic interaction by considering the gap distance, the presence of number of neighboring structures and the wave direction headings. In order to analyze the added mass, radiation damping and motion responses that are developed during the interaction between structures, commercial software ANSYS AQWA is used. The analysis are executed by using 100 m diameter of round-shaped FPSO as the reference point for a single body where it is compared with two bodies and three bodies by using 70 m diameter round-shaped FPSO and LNG vessel for gap distance of 25 m and 50 m and wave directions at 00, 450, 900, 1350 and 1800 headings. The results show same trend with previous studies and researches in which the motion responses due to the effect from other structures occur significantly on surge and pitch motions compare to heave mot ion though there are small interactions. As for overall, the gap distance between structures, the presence of number of neighboring structures and the wave directions affect the motions of multiple bodies of offshore structures due to hydrodynamic interaction.